Persepsi Siswa Kelas V Terhadap Materi Bela Diri Pencak Silat Di SD Negeri 81 Kecamatan Jakabaring - Azwan Zainuri; Farizal Imansyah; Ilham Arvan Junaidi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Early introduction is the first step to introduce and develop pencak silat in Indonesia. What can be done is to include pencak silat material in elementary schools. The aim of this research is to determine the perceptions of class V students regarding pencak silat martial arts material at SD N 81, Jakabaring District. The method used in this research is a quantitative descriptive method. The research population was 40 class V students of SD N 81 Jakabaring District. So the sample for this study was 40 people and 30 people were the trial sample. The data collection technique was carried out using a research questionnaire. The data collection instrument is a questionnaire with 50 statements which have been tested as valid statements to be used as research instruments. The data analysis technique is carried out using percentage analysis. The results can be concluded that the perception of class V students at SD N 81 Jakabaring District towards the pencak silat martial arts material is 73.42% in the good category.